48-3=6-10x

Simple and best practice solution for 48-3=6-10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48-3=6-10x equation:


Simplifying
48 + -3 = 6 + -10x

Combine like terms: 48 + -3 = 45
45 = 6 + -10x

Solving
45 = 6 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
45 + 10x = 6 + -10x + 10x

Combine like terms: -10x + 10x = 0
45 + 10x = 6 + 0
45 + 10x = 6

Add '-45' to each side of the equation.
45 + -45 + 10x = 6 + -45

Combine like terms: 45 + -45 = 0
0 + 10x = 6 + -45
10x = 6 + -45

Combine like terms: 6 + -45 = -39
10x = -39

Divide each side by '10'.
x = -3.9

Simplifying
x = -3.9

See similar equations:

| 3(4a-1)=7(2a-7) | | -8(x+1)=4(x-1) | | -10(s+3)=-43 | | -(c+6)=1 | | 2(x-4)+3(2-x)+2x+2= | | 7(2l+8)=122 | | 2x-45=90 | | X^5=230 | | x^3-27x^2+12=0 | | 0.43=0.0814ln(x)+0.3357 | | 3sin(x)-2cos(x)=0 | | a-2a-3=0 | | -3y=5t | | x+10-16=1 | | 3*b-b*(-3)+3*(-b)= | | 3X-21=4X-36 | | Ln*(x-4)+ln*(x-7)=ln*18 | | 3xb-bx(-3)+3x(-b)= | | 1/3k-1=4/6 | | In*(x-6)+In*(x-4)=In*15 | | 6x-9-4x=13 | | (4y+7)(4-y)=0 | | q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 |

Equations solver categories